Targeting Ionotropic Glutamate Receptors in the Treatment of Epilepsy - Celli, Roberta; Fornai, Francesco (Current Neuropharmacology, 2021)
Background: A dysfunction in glutamate neurotransmission is critical for seizure. Glutamate is the major excitatory drive in the cerebral cortex, where seizures occur. Glutamate acts via (i) ionotropic (iGlu) receptors, which are ligand-gated ion channels mediating fast excitatory synaptic transmission; and (ii) G proteins coupled metabotropic (mGlu) receptors. Objective: To overview the evidence on the role of iGlu receptors in the onset, duration, and severity of convulsive and non-convulsive seizures to lay the groundwork for novel strategies for drug-resistant epilepsy. Methods: We used PubMed crossed-search for “glutamate receptor and epilepsy” (sorting 3,170 reports), searched for “ionotropic glutamate receptors”, “AMPA receptors”, “NMDA receptors”, “kainate receptors”, “convulsive seizures”, “absence epilepsy”, and selected those papers focusing this Review’s scope. Results: iGlu receptor antagonists inhibit, whereas agonists worsen experimental seizures in various animal species. Clinical development of iGlu receptor antagonists has been limited by the occurrence of adverse effects caused by inhibition of fast excitatory synaptic transmission. To date, only one drug (perampanel) selectively targeting iGlu receptors is marketed for the treatment of focal epilepsy. However, other drugs, such as topiramate and felbamate, inhibit iGlu receptors in addition to other mechanisms. Conclusion: This review is expected to help dissect those steps induced by iGlu receptors activation, which may be altered to provide antiepileptic efficacy without altering key physiological brain functions, thus improving the safety and tolerability of iGlu-receptor directed antiepileptic agents. This effort mostly applies to drug resistant seizures, which impact the quality of life and often lead to status epilepticus, which is a medical urgency.
Keywords: convulsive seizures